2020
DOI: 10.2147/prbm.s226722
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Characteristics of Moral Judgment of Psychopaths: The Mediating Effect of the Deontological Tendency</p>

Abstract: Purpose: Many studies explore the relationship between moral judgment and psychopathy in western culture, but the mechanism underlying this relationship remains unclear. By far, no research about this topic in the background of Chinese culture exists. In the current study, we adopt one of the creative process-dissociation approaches to explore the relationship between the psychopath and moral judgment. Methods: Adopt the Levenson Self-Report Psychopathic Scale, the Chinese version of Interpersonal Reactivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…This evidence supports that a bias to utilitarian consideration contributes to moral judgment as the brain’s emotional system is impaired 11 . Similar findings have been reported in subclinical populations with emotional deficits that predict utilitarian judgement 12 , such as individuals with high levels of alexithymia 13 .…”
Section: Introductionsupporting
confidence: 86%
“…This evidence supports that a bias to utilitarian consideration contributes to moral judgment as the brain’s emotional system is impaired 11 . Similar findings have been reported in subclinical populations with emotional deficits that predict utilitarian judgement 12 , such as individuals with high levels of alexithymia 13 .…”
Section: Introductionsupporting
confidence: 86%
“…It is argued that these deficiencies diminish the automatic emotional processes, causing a bias towards the controlled cognitive processes, favoring utilitarian choices. This is however only confirmed in relation to psychopathic traits in community samples [ [29] , [30] , [31] ] while studies in confirmed psychopathic individuals show mixed results [ 32 , 33 ], which is arguably due to the different levels of emotion associated with utilitarian behavior in these studies.…”
Section: Introductionmentioning
confidence: 77%